Caesarean section and left femur fracture in breech presentation in a primipara - Pranav Kumar Dave; P Chouhan; V Gupta; R Mishra; M Jain; M Bapat; M Tilgam; A Patidar; P Patil; C Dave; SA Faruqui (Barpeta Obstetrics and Gynaecological Society, 2020)
Fracture of femur of new born is rare during normal delivery or caesarean section. It may occur in difficult delivery in new born or after caesarean section due to unnoticed trauma at the time of extraction of baby. Usually noticed immediately after birth as swelling of thigh. We report the case of a female new born caesarean section delivered with fracture of left femur in primipara with breech presentation.